The Prevention of Children as Victims of Human Trafficking - Nursariani Simatupang (Randwick International of Social Science Journal, 2021)
Trafficking in persons is a crime that often occurs. Children are very vulnerable to become victims of human trafficking. Child trafficking is an act that is very inhumane and destroys the future of children. Child trafficking is usually carried out by persuasion, making promises, and deceiving the victims. Therefore, precautions must be taken to minimize child trafficking. To prevent this, several efforts were made, including improving the family economy, creating a harmonious family, increasing religious understanding, negative impacts and legal consequences of child trafficking, increasing supervision on children, keeping children away from hedonistic lifestyles and consumptive behavior, getting to know children's social environment, increasing children's education and skills.